Analisis determinan deposito mudharabah - Sulistyawati, Ardiani Ika; Hidayah, Nurul; Santoso, Aprih (Indonesia Accounting Journal, 2020)
The objective of this study is to test the influence of inflation rates, interest rates, liquidity rates proxied by the finance to deposit ratio, and profit sharing rates to the amount of mudharabah deposit. This study conducts the regression analysis and uses time series data which retrieved from the quarterly financial statements of BRI Syariah and BCA Syariah in Indonesia over period of 2014 to 2018 as the sample. The study proves that: (a) the inflation rates is insignificant to influence the amount of deposit mudharabah; (b) the interest rates is insignificant to influence the amount of deposit mudharabah of BRI Syariah and BCA Syariah because when the interest of conventional bank increase then the amount of deposit mudharabah do not experience dramatic changes because the customers still invest their fund at BRI Syariah and BCA Syariah; (c) finance to deposit ratio is significant to influence the amount of mudharabah deposit; (d) the rates of share profit is insignificant to influence the amount of mudharabah deposit; and (e) size is insignificant to influence the amount of mudharabah deposit.